2017
DOI: 10.1371/journal.pone.0172183
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D status in pediatric irritable bowel syndrome

Abstract: ImportanceIrritable bowel syndrome (IBS) is associated with significant morbidity in children and adolescents, and the therapeutic efficacy of available treatment options is limited. The role of vitamin D supplementation in pediatric IBS is unclear as the vitamin D status of pediatric patients with IBS is unknown. Equally, the relationship of vitamin D status with psychosomatic symptoms in children and adolescents is unclear.AimTo characterize the vitamin D status of pediatric patients with IBS using a case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
1
22
0
2
Order By: Relevance
“…Vitamin D deficiency or insufficiency has been estimated to affect about 1 billion people worldwide [16]. Vitamin D deficiency is more common in IBS patients than in a healthy population, and studies have shown that the severity of the symptoms is inversely correlated with serum vitamin D concentration [17][18][19][20]. Moreover, studies demonstrated that vitamin D deficiency is related to symptoms of psychological disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency or insufficiency has been estimated to affect about 1 billion people worldwide [16]. Vitamin D deficiency is more common in IBS patients than in a healthy population, and studies have shown that the severity of the symptoms is inversely correlated with serum vitamin D concentration [17][18][19][20]. Moreover, studies demonstrated that vitamin D deficiency is related to symptoms of psychological disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while commonly associated with its role in Ca 2+ /PO 4 3-homeostasis, vitamin D is crucial in the modulation of a variety of other pathways, including those involved in anti-inflammatory and immunomodulatory activity. 22 Thus, vitamin D has been proposed as a potential treatment for IBS 23 as well as IBD. 24 Moreover, in a recent report, the production of the rate-limiting enzyme in serotonin production, TPH, was significantly stimulated by the active hormonal vitamin D metabolite, 1,25-dihydroxyvitamin D (1,25D), in serotonergic neurons.…”
mentioning
confidence: 99%
“…The areas of the gut involved in vitamin D absorption is centered predominantly in the ileum (70-80%) [10] , with most of the vitamin D receptors and regulatory mechanisms in the cecum and colon regions, the importance of vitamin D deficiency needs to be addressed seriously in IBS patients as well [11,12] . Nwosu [13] . Also, In study of and vitamin D level was found [14] .…”
Section: Discussionmentioning
confidence: 99%